Academic outcomes of a community-based longitudinal integrated clerkships program - Latessa, Robyn; Beaty, Norma; Royal, Kenneth; Colvin, Gaye; Pathman, Donald E.; Heck, Jeffery (Medical teacher, 2015)
Background: Longitudinal integrated clerkships (LICs) receive recognition internationally as effective, innovative alternatives to traditional block rotations (TBRs) in undergraduate medical education. No studies of LICs in the USA have assessed how students perform on all the standardized exams. Aim: To compare performance on standardized tests of students in the first four years of LICs at the University of North Carolina School of Medicine-Asheville (UNC SOM-Asheville) with students from UNC SOM's Chapel Hill main campus in TBRs. Methods: LIC and TBR students' previous academic performance was considered using Medical College Admissions Test (MCAT) and United States Medical Licensing Examination (USMLE) Step 1 scores. Step 1 exam tests students' pre-clinical, basic science knowledge. Outcome measures included all eight standardized National Board of Medical Examiners (NBME) Subject Shelf Examinations and USMLE Step 2 Clinical Knowledge (CK) examinations, which are used widely in the US to assess students' progress and as prerequisites to eventual licensure. TBR students were selected using propensity scores to match LIC students. Groups were also compared on the required core clinical conditions documented, and on residency specialty choice. Results: Asheville LIC students earned higher scores on the Step 2 CK examination and the six shelf examinations linked to longitudinal clerkships than the matched TBR students (Step 2 CK exam, Family Medicine and Ambulatory Medicine shelf exams reached statistical significance). LIC students logged greater percentages of core conditions than TBR students and more often chose primary care residencies. Conclusions: UNC School of Medicine medical students participating in a longitudinal integrated curriculum in a community setting outperformed fellow students who completed a more TBR curriculum within the school's academic medical center. Differences were found in performance on standard tests of clinical knowledge (six NBME exams and Step 2 CK exam), documented breadth of clinical experiences, and likelihood of choosing primary care residency programs.